ARTIFICIAL INTELLIGENCE APPLIED TO SUPPLY CHAIN MANAGEMENT IN A BAKERY INDUSTRY: A CASE STUDY WITH SAP BUSINESS ONE (REMUNOM, 2025)
The increasing complexity of supply chains requires solutions that integrate agility, predictability, and cost reduction. This study aims to analyze the application of Artificial Intelligence (AI) in a medium-sized bakery industry in Minas Gerais, Brazil, through the implementation of SAP Business One software. The research is applied in nature, with a qualitative and quantitative approach. Semi-structured interviews with the supply chain manager and analysis of indicators before and after system adoption were conducted. Results showed significant improvements: increased inventory accuracy, reduced losses, greater reliability in demand forecasting, and cross-sector integration. It is concluded that AI application in supply chain adds competitive advantage and operational efficiency, being a viable alternative for traditional industries.